Tension‐referenced measures of gastrocnemius slack length and stiffness in Parkinson's disease. Issue 12 (11th March 2016) - Tan, Benedict; Double, Kay L; Burne, John; Diong, Joanna
Abstract: Background: It is not known how passive muscle length and stiffness contribute to rigidity in Parkinson's disease. The objective of this study was to compare passive gastrocnemius muscle‐tendon slack length and stiffness at known tension in Parkinson's disease subjects with ankle rigidity and in able‐bodied people. Methods: Passive ankle torque‐angle curves were obtained from 15 Parkinson's disease subjects with rigidity and 15 control subjects. Torque‐angle data were used to derive passive gastrocnemius length‐tension data and calculate slack length and stiffness of the gastrocnemius muscle. Between‐group comparisons were made with linear models. Results: Gastrocnemius muscle‐tendon slack lengths (adjusted between‐group difference, 0.01 m; 95% CI, ‐0.02 to 0.04 m; P = 0.37) and stiffness (adjusted between‐group difference, 15.7 m ‐1 ; 95% CI, ‐8.5 to 39.9 m ‐1 ; P = 0.19) were not significantly different between groups. Conclusions: Parkinson's disease subjects with ankle rigidity did not have significantly shorter or stiffer gastrocnemius muscles compared with control subjects. © 2016 International Parkinson and Movement Disorder Society